Core-shell structure: An effective feature for strengthening ZrB2 ceramics. (February 2019) - Silvestroni, Laura; Failla, Simone; Vinokurov, Vladimir; Neshpor, Irina; Grigoriev, Oleg
Abstract: Hot compression behavior of two ZrB2 ceramics containing SiC or WSi2 particles was investigated upon stepwise heating from 1700 to 2100 °C under static load in vacuum. Presence of SiC activated notable creep already at 1700 °C, owing to diffused silica softening at SiC/SiC interfaces, whilst for WSi2 appreciable deformation occurred only above 1900 °C. Limited amount of SiC particles, which is responsible for cavitation, and formation of (Zr, W)B2 solid solution, able to accommodate high mechanical loads through plastic deformation, are fundamental characteristics to remarkably perform in hot environments. Particularly, dislocation activity in the solid solution plays a fundamental role at ultra-high temperatures. Graphical abstract: